SUPERVISI DALAM PEMBELAJARAN DI MADRASAH - Imran Siregar (Badan Litbang dan Diklat Kementerian Agama RI, 2007)
AbstractIn the learning process in madrasah, a supervisor has an important role in achieving the learning objective. He is a partner, consultant, and an evaluator as well. Consequently, the madrasah supervisor has to have wider knowledge and experience for carrying his task and responsibilities.This research tries to describe how the madrasah’s supervisor carries his task and responsibility in teaching-learning process.The research finds out that the role of madrasah supervisor-whether as partner, consultant, or evaluator-has not fully been functional. Yhis condition is dominantly caused by the knowledge, experience, and training background of the supervisor which is mostly irrelevant to his job. Another factor is related to the age of supervisor which is approximately near to 60 years, that become a constraint to actively encourage his quality improvement.